ANALISIS YURIDIS TERHADAP PEMBULATAN TARIF PEMBAYARAN JUAL BELI ONLINE PADA METODE COD (Cash On Delivery): (Tinjauan Menurut Hukum Perjanjian Jual Beli) - Imroatus Sholihah; Eva Maratus Sholihah; Sumriyah Sumriyah (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The practice of rounding in the COD system occurs quite often around, this rounding can occur many times each time the COD process is carried out. Sometimes the rounding is rounded up, but usually it is also rounded down, but this is quite rare. This research aims to determine the legal relationship between couriers and buyers and the responsibility of couriers in the COD system for rounding which often occurs in the area. The author uses a normative approach and examines related laws, the author also conducts interviews with related people who have been victims of nominal rounding in the COD system. In civil law the courier and the buyer have a binding legal relationship, where the courier is obliged to deliver the goods to their destination and the buyer is obliged to give money for the goods. in his responsibility the courier must have good faith in the legal relationship.